Asymmetrical handgrip strength and body composition of cadet wrestlers: a pilot study - Torres-Álvarez, Y. L.; Miarka, B.; Padilla, J. R.; Lozada-Medina, J. L.; Gamardo Hernández, P. F. (International Journal of Wrestling Science, 2020)
Purpose: to compare the body composition and the maximum of handgrip strength of Venezuelan cadet wrestlers. The sample was of ten wrestlers of Greco-Roman (GR=5; M±SD, age: 16.81±0.34 yrs.-old; weight: 58.76±4.43 kg; height: 167.2±0.31 cm) and Freestyle (FS=5; M±SD, age: 16.35±0.59 yrs.-old; weight: 60.92±3.34 kg; height: 166.7±0.39 cm). Methods: the procedure used to estimate the body composition (BC) followed the established standards by the International Society for the Advancement of Kinanthropometry. The handgrip strength (HGS) was measured using the manual dynamometer (Takei), recording the best value of three (3) attempts for both right and left hand. The "t Student" was used to compare GR vs. FS wrestlers and to verify statistical differences between the strength of handgrip (left and right), p =0.05 value. Results: No effects were observed between GR and FS; the reported values of BC were 12.98±3.08 % for the % body fat and 52.07±3.73 kg for the fat-free mass. The handgrip strength was registered in absolute and relative terms to body weight having as a result for the right hand: (HGS: 49,70±3,53kg.s; 0,83±0,41Kg·kg.s-1) and the left hand (HGS: 43,90±4,07kg.s; 0,74±0,05Kg·kg.s-1). Significant differences were found between the (HGS) of the right hand compared with the left hand (absolute, p =0.05; relative, p =0.05). Conclusion: The differences obtained in the (HGS -asymmetrical) could be due to the predominance of the right hand in relationship with the left hand, or to the actions performed with greater emphasis of the right handed side in this group of wrestlers.